Optimized “In Vitro” Culture Conditions for Human Rheumatoid Arthritis Synovial Fibroblasts - Casnici, Claudia; Lattuada, Donatella; Tonna, Noemi; Crotta, Katia; Storini, Claudio; Bianco, Fabio; Truzzi, Marcello Claudio; Corradini, Costantino; Marelli, Ornella (Mediators of Inflammation, 2014)
The composition of synovial fluid in rheumatoid arthritis (RA) is complex and strongly influences the microenvironment of joints and it is an inseparable element of the disease. Currently, “in vitro” studies are performed on RA cells cultured in the presence of either recombinant proinflammatory cytokines-conditioned medium or medium alone. In this study, we evaluated the use of synovial fluid, derived from RA patients, as optimal culture condition to perform “in vitro” studies on RA synovial fibroblasts. We observed that synovial fluid is more effective in inducing cell proliferation with respect to TNF-alpha or culture medium alone. Spontaneous apoptosis in fibroblasts was also decreased in response to synovial fluid. The expression of proinflammatory cytokines in the presence of synovial fluid was significantly elevated with respect to cells cultured with TNF-alpha or medium, and the overall morphology of cells was also modified. In addition, modulation of intracellular calcium dynamics elicited in response to synovial fluid or TNF-alpha exposure is different and suggests a role for the purinergic signalling in the modulation of the effects. These results emphasize the importance of using RA synovial fluid in “in vitro” studies involving RA cells, in order to reproduce faithfully the physiopathological environmental characteristic of RA joints.